First study of single-event burnout in very-thin planar silicon sensors - Ferrero, Marco; Arcidiacono, Roberta; Cartiglia, Nicolò; Lanteri, Leonardo; Menzio, Luca; Morozzi, Arianna; Moscatelli, Francesco; Mulargia, Roberto; Siviero, Federico; White, Robert; Sola, Valentina (Frontiers in Physics, 2025)
This paper investigates the single-event burnout (SEB) effect in thin irradiated positive-intrinsic-negative (PiN) diodes and low-gain avalanche diodes (LGAD). SEB is a destructive event triggered in silicon sensors by the passage of a high-momentum charged particle. This effect arises in planar sensors under specific conditions: a significant ionization event caused by the particle’s passage and a very high electric field in the entire bulk region. The investigation of SEB was performed in two beam test campaigns: one at Deutsches Elektronen-Synchrotron (DESY) with an electron beam of 3.6  GeV/c momentum and the second at CERN with a pion and proton beam of 120  GeV/c momentum. The sensors under test had active thicknesses from 15  μm to 55  μm and active surfaces from 1.7  mm2 to 433  mm2. In preparation for this study, most sensors were irradiated with neutrons up to a fluence of 1⋅1016  neq/cm2. The experimental setup for the beam tests included a frame for the alignment of the sensor with six available slots, two of which were equipped with trigger boards to monitor the beam rate during the test campaigns. This frame was placed inside a cold box to operate the irradiated sensors at very high electric fields while keeping their leakage current low. The experimental results show an inversely proportional relationship between the electric field at the SEB (SEB field) and the active thickness of the sensors. In this study, the SEB field increases from 11-12 V/μm in a 55-μm-thick sensor to 14 V/μm in a 15–20 μm-thick sensor.